Integration of a membrane bioreactor to nanofiltration/reverse osmosis for treatment of emergin pharmaceuticals in domestic wastewater - Alobaidi, Raghad Asad Kadhim (My University, 2021)
Though conventional biological treatment plants can remove the basic pollutants, they are found to be ineffective in removing recalcitrant pollutants. Membrane bioreactors are considered a promising technology by having advantages such as higher effluent quality and producing low sludge in comparison to conventional biological treatment processes. In this study, the elimination of pharmaceutical compounds was investigated by membrane bioreactors under different solid retention time (SRT). The effect of SRT on the elimination of emerging pharmaceuticals was observed for 20, 30, and 40-day SRT and monitored for 96 days for each and, it was found that the 40-day SRT had the optimum performance in terms of the pharmaceuticals’ elimination. Chemical oxygen demand (COD) removal efficiencies for each selected SRT were higher than 96% at steady-state conditions. The highest degradation efficiencies were observed for paracetamol, and when it is sorted from the most removed compound towards the lowest, it can be listed as Paracetamol, Ranitidine, Atenolol, Bezafibrate, Diclofenac, Carbamazepine. The microbial community at the phylum level was also analyzed to understand the biodegradability of pharmaceuticals. It was noticed that the proteobacteria phylum increased from 46.8% to 60.0% after 96 days after adding the pharmaceuticals. Actinobacteria class which can metabolize paracetamol, carbamazepine, and atenolol was also increased from 9.1% to 17.9% after adding pharmaceuticals. The by-products of diclofenac, bezafibrate, and carbamazepine were observed in the effluent samples. The transmembrane pressure TMP was monitored during the whole work period and it was observed that during the 20 day SRT phase, the fouling occurred much more often and faster for both 0.2 µm and 0.45 µm membranes than the fouling occurred during the 30 and 40 day SRT phases. This might be due to the increase in the values of SMP and EPS when decreasing the SRT. The combination of MBR treatment to the NF270, NF90 and RO membranes resulted in the removal of four pharmaceuticals (paracetamol, ranitidine, atenolol, and bezafibrate) to below detection limits. In addition, it's worth noting that when the BW30 was used in conjunction with the MBR treatment, the removal efficiency for diclofenac and carbamazepine was higher than other membrane combinations recording about 86% and 82% respectively.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Membrane bioreactor; Pharmaceuticals; By-products; Solid retention time; Solid phase extraction